Strategi Guru Untuk Meningkatkan Kemampuan Membaca Siswa Kelas IV Sekolah Dasar Negeri 15 Pagaruyung - Soniah; Safrizal; Elda Herlina (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The historical past of this research is one of the trainer's strategies to improve simple college students' studying capabilities. This takes a look at ambitions to explain the trainer's approach to enhancing students' reading talents. This form of research is a qualitative description. The informants in this examination were school principals and teachers at faculty. the important thing instrument itself is the researcher himself when the implementation is assisted with the aid of interview publications, commentary sheets, and tape recorders. facts series is finished by way of interviews, observation, and documentation. records evaluation changed into carried out using the Miles and Huberman model along with facts discount, records show, and additionally conclusions. The validity of the facts with records triangulation techniques. The consequences of the research display that the strategies used to enhance studying abilities are by using studying literacy, spelling methods, and good-sized analyzing. therefore it could be concluded that this use can enhance analyzing abilities.